Maturity Analysis Of Knowledge Management Implementation On Organizational Performance (Survey On State-Owned Enterprises In Indonesia) - SUWARSI, SRI; HARAHAP, DEDY ANSARI; AMANAH, DITA (The journal of contemporary issues in business and government, 2021)
Knowledge Management (KM) implementation has taken place several decades ago in many companies in the world, including companies in Indonesia. The purpose of this study was to measure how the maturity level of KM implementation and organizational performance, also how the influence of achieving the maturity level of KM implementation on organizational performance. Research method used is explanatory research, the sampling technique used is the method Proportional Stratified Random Sampling. The unit of observation was 283 respondents, consisting of 47 middle managers, 81 lower managers, and 155 employees. The results showed that the maturity level of KM implementation using 7 dimensions, namely knowledge creation, knowledge retention, knowledge transfer and knowledge utilization, management and leadership support, corporate entrepreneurship and application technology are at a superior level or a level of good achievement.